Research on Academic Giftedness of Future Teachers - Kariyev , Adlet; Orazbayeva , Fauziya; Imankulova , Meruyert; Vasileva , Valentina (Insight: the psychological dimensions of society, 2024)
The aim of the research is to establish psychological content parameters, correlations and factors of future teachers’ academic giftedness. It was assumed that personal factors of future teachers’ academic giftedness would have statistically significant correlations with academic performance and parameters of intelligence; the researched groups distributed by academic performance evaluation would have significant differences by personal factors of academic giftedness, verbal, mathematical and spatial intelligence. Methods. The research participants were the 2nd–4th year full-time students pursuing a degree in pedagogy at three higher education institutions: two institutions from Kazakhstan – Abai Kazakh National Pedagogical University (Abai KNPU), Auezov South Kazakhstan University (Auezov SKU) and one institution from Bulgaria – “Angel Kanchev” University of Ruse (RU “Angel Kanchev”), numbering 258 people aged from 18 to 22 years. The method for diagnosing personal factors of giftedness (PFG) (Belskaya, 2019); “Intelligence structure test” (IST 2000) (Amtchauer et al., 2001) were applied. An additional variable – academic performance evaluation (APE) – was used. Results. Pearson’s correlation analysis (R) allowed establishing fifteen correlations (р ≤ .050; р ≤ .010; p < .001) between the factors of academic giftedness, the types of intelligence and academic performance evaluation. It was found that the factor of giftedness “over-situational activeness” has the largest number of significant correlations – four (p < .001; р ≤ .050). It was substantiated that this factor is the most important and the most dependent one in future teachers’ academic giftedness. The Mann-Whitney U-test allowed establishing a statistically significant advantage of Group 2 (a high level of academic performance evaluation) by the parameter “over-situational activeness” (U = 6340.000; p < .040). It was explained that the respondents’ over-situational activeness is a backbone factor of future teachers’ academic giftedness. Discussion and conclusions. The obtained empirical results and the established statistically significant correlations and differences possess scientific novelty and applied value. A number of recommendations concerning reorganization and implementation of innovative processes of training future teachers aimed at developing academic giftedness and providing quality psychological-pedagogical support for gifted students were made.